New Liquid Chemical Hydrogen Storage Technology - Xinchun Yang; Dmitri A. Bulushev; Jun Yang; Quan Zhang (Energies, 2022)
The liquid chemical hydrogen storage technology has great potentials for high-density hydrogen storage and transportation at ambient temperature and pressure. However, its commercial applications highly rely on the high-performance heterogeneous dehydrogenation catalysts, owing to the dehydrogenation difficulty of chemical hydrogen storage materials. In recent years, the chemists and materials scientists found that the supported metal nanoparticles (MNPs) can exhibit high catalytic activity, selectivity, and stability for the dehydrogenation of chemical hydrogen storage materials, which will clear the way for the commercial application of liquid chemical hydrogen storage technology. This review has summarized the recent important research progress in the MNP-catalyzed liquid chemical hydrogen storage technology, including formic acid dehydrogenation, hydrazine hydrate dehydrogenation and ammonia borane dehydrogenation, discussed the urgent challenges in the key field, and pointed out the future research trends.